Pengaruh Kepemimpinan Transformasional Terhadap Kinerja Karyawan Pada PT. Wom Finance Makassar - Tokii, Olov; Baharuddin, Baharuddin; Tandirerung, Ch Jeane (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Transformational leaders can inspire and motivate their followers. This offers an approach that is different from conventional leadership approaches. Transformational leaders not only focus on supervision and control; they also pay attention to the growth potential of each employee. They strive to create clear and engaging goals and build strong team connections. This leadership style can help PT WOM Finance improve employee discipline more humanely. to understand how the performance of PT WOM Finance employees is influenced by transformational leadership. This research was conducted quantitatively with a sample of 47 employees. Validity Test, t-Test, coefficient of determination (r2), and correlation coefficient test were used as data analysis techniques. This research was conducted using SPSS, which measures the performance of employees at PT. WOM Finance Makassar is influenced by 26% by the transformational leadership variable, also known as X. The correlation test between variable X and Y is significant. The employee performance variable is explained by 26% of the determinant of variable X, transformational leadership. Other variables not examined by the researcher affect the remainder. According to the t-test of the transformational leadership variable (X), the significance value of 0.001 is less than 0.05, and the calculated value of 4.187 is greater than the t-table value of 2.011. Thus, H1 can be accepted.